EFEKTIVITAS MEDIA QUIZIZZ DALAM MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPAS SISWA SEKOLAH DASAR - Wahyudi, Wahudi; Yoga Prihatin; Sutji Muljani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of Quizizz learning media in improving the activity and learning outcomes of IPAS material on force and motion in fifth grade elementary school students. The research method used a true-experimental design with a pretest-posttest control group design. The research subjects were fifth-grade students at SDN 02 Sokawangi (experimental class, n=22) and SDN 03 Sokawangi (control class, n=22). The research instruments included a learning activity observation sheet and a learning outcome test (20 multiple-choice questions). The data were analysed using descriptive statistics, normality test (Shapiro-Wilk), homogeneity test (Levene Test), t-test (Independent Sample T-Test), and N-Gain. The results showed that Quizizz was effective in increasing learning activity from 46.5% to 87% (an increase of 40.5%), with the emotional aspect recording the highest increase (57%). The learning outcomes of the experimental class increased with an N-Gain of 0.42 (moderate category), significantly higher than the control class (N-Gain 0.25; low category). The t-test showed a significant difference between the experimental and control classes (t=2.757; df=43; p=0.008<0.05). The classical mastery of the experimental class reached 64% compared to 52% in the control class. The study concluded that Quizizz is effective as an IPAS learning innovation that not only improves cognitive learning outcomes but also builds intrinsic motivation and student activity through enjoyable and meaningful learning experiences.